ENDOSCOPIC SUBMUCOSAL DISSECTION WITH CIRCUMFERENTIAL INCISION VERSUS TUNNELING METHOD FOR TREATMENT OF SUPERFICIAL ESOPHAGEAL CANCER - RIBEIRO,Tarso Magno Leite (2021)
ABSTRACT BACKGROUND: Endoscopic submucosal dissection (ESD) of esophageal superficial neoplasm is associated with a high en bloc R0 resection rate and low recurrence. OBJECTIVE: We aim to compare the performance and clinical outcomes of ESD via ESD after circumferential incision (ESD-C) versus submucosal tunneling (ESD-T). METHODS: Single-center retrospective analysis of all consecutive patients who underwent ESD for superficial esophageal cancer, between 2009 and 2018. ESD-T was defined as the technique of making the mucosal incisions followed by submucosal tunneling in the oral to anal direction. ESD-C consisted of completing a circumferential incision followed by ESD. Main study outcomes included en bloc and R0 resection rates. Secondary outcomes included procedural characteristics, curative resection rate, local recurrence and adverse events. RESULTS: A total of 65 procedures (23 ESD-T and 42 ESD-C) were performed for ESCC (40; 61.5%) and BE-neoplasia (25; 38.5%). There were no statistically significant differences between patients who underwent ESD-T versus ESD-C in en bloc (91.3% vs 100%, P=0.12), R0 (65.2% vs 78.6%, P=0.24), curative resection rates (65.2% vs 73.8%, P=0.47) and mean procedure time (118.7 min with vs 102.4 min, P=0.35). Adverse events for ESD-T and ESD-C were as follows: bleeding (0 versus 2.4%; P=0.53), perforation (4.3% vs 0; P=0.61), esophageal stricture (8.7% versus 9.5%; P=0.31). Local recurrence was encountered in 8.7% after ESD-T and 2.4% after ESD-C (P=0.28) at a mean follow-up of 8 and 2.75 years, respectively (P=0.001). CONCLUSION: ESD-T and ESD-C appear to be equally effective with similar safety profiles for the management of superficial esophageal neoplasms.